Register role and function in the arena of sociocultural practice (critical study of sociocultural practice) - Sujarwa, Sujarwa; Purwasito, Andrik; Habsari, Sri Kusuma; Pitana, Titis Srimuda (BAHASTRA, 2023)
This paper is entitled "The Role and Function of the Register in the Arena of Sociocultural Practices". This theme was raised because in the arena of sociocultural communication practices there is a hidden peculiarity in the form of deception, which is often inconsistent between linguistic aspects and sociocultural behavior. The use of the register as a style of communication rhetoric is built not without reason but contains the motives, intentions, achievements to be achieved. This paper aims to reveal: the form of the register, the role and function of the register, as well as the symbolic meaning of the register in the arena of sociocultural communication practices in the cattle trade. For this reason, a qualitative descriptive method is needed, which attempts to substantially describe aspects of the meaning of the data with in-depth analysis related to the subject matter. In order to arrive at an in-depth interpretation, the following theoretical knowledge is used: sociocultural, sociolinguistic, capitalism, hegemony, hegemonic, and hermeneutic as a strategic method for understanding texts whose meaning must be interpreted. The results of the study indicate: there are forms of oratorical, deliberative, consultative, casual, intimate registers. The function of the register is to act as an instrument of conative and emotive manipulation to influence, weaken, subdue, and restrain hegemonic control or domination. The register has a symbolic meaning of feudalism relations in the form of a phenomenon in the arena of sociocultural communication practices influenced by the discourse on capitalist cultural domination.